The insecticidal activity of some plant-seeds extracts against two coleopteran pest Granary Weevils Sitophilus Granarius(Linnaeus.) and the Lesser Grain Borer Rhyzopertha Dominica (Fabricius) - K.M. Mohanny; A.E. Abd El-Aziz; G. Mohamed; W.A.A. Abazied (SVU-International Journal of Agricultural Sciences, 2020)
Acetone and petroleum ether seed extracts of fennel [Foeniclum vulgare, Apiaceae] and arugula seeds [Eruca vesicaria, Brassicaceae] were tested for their contact and stomach poison activity on adults the granary weevil Sitophilus granarius Linnaeus. (Coleoptera: Curculionidae) and lesser grain borer Rhyzopertha  dominica Fabricius. (Coleoptera: Bostrochidae). The results revealed that, percentage of mortality increased with increasing the concentration of different extracts and exposure time. Extracts of arugula seeds of petroleum ether and acetone gave higher mortality percent compared with the extracts from fennel seeds. Petroleum ether and acetone extract of arugula seeds was founded to be the higher effect on the two species insect than the fennel seeds extracts. The LC50 of arugula seed extracts of petroleum ether and acetone ranged from 0.722, 0.620, 0.622 and 0.475 ml/ kg after 5 days treatment against R. dominica and S. granarius, respectively. On the other hand, these values of fennel seeds extract ranged from 1.331, 0.798, 1.093 and 0.662 for R. dominica and S. granarius, Respectively. While the higher concentration 1.5 and 2 % (W/V) give complete mortality at two extracts against two insects. The petroleum ether of fennel seeds extract with R. dominica give 73.3 and 83.3 % after 14 days treatment. The inhibition rates in the reduction of the first generation (F1-progeny) of R. dominica and S. granarius adults in grains treated with various extracts were higher than mortality at all concentrations to all extract.